An electrochemical-irradiated plasticity model for metallic electrodes in lithium-ion batteries - Ma, Z.; Wu, H.; Wang, Y.; Pan, Y.; Lu, Chunsheng (Elsevier, 2017)
Lithium-ion batteries (LIBs) in space or extreme environments may suffer irradiation and during operation, it is difficult to obtain the intrinsic mechanical properties of electrode materials due to coexistence of electrochemical reaction and irradiation. In this paper, effects of irradiation temperature, dose, and diffusion-induced stress on their mechanical behaviors are explored. By introducing diffusion-induced stress, an electrochemical-irradiated plasticity model is developed for electrodes in cylindrical LIBs, which is validated by comparing numerical results with experimental data. It is shown that the yield strength of unirradiated active materials decreases with increasing the state of charge, which is attributed to the softening behavior from electrochemical reactions in a diffusion process of Li-ions. For irradiated active materials, the yield strength increases with increasing irradiation dose due to irradiation-induced defects; however, it decreases with irradiation temperature. Such a model can be applied to build up the stress-strain relations of composite electrodes and to provide a guideline for assessing their mechanical behaviors during different states of charge in LIBs.